WAYS TO IMPROVE DIGITAL FINANCIAL SERVICES IN COMMERCIAL BANKS (Conferencea, 2023)
A lot of information circulates around the world every day. This is due to the constantly growing technical capabilities of the Internet and mobile phones, the involvement of people in social networks, and the year-by-year increase in Internet speed. Today, as a result of significant changes in the field of digitization, we can also observe changes in the economy, finance and banking. In addition, the residents of our country can perform any card-to-card (P2P) money transfer (P2P) transactions, budget, tax, utility and other payments, repay loans, receive microloans and online through the mobile application programs of digital banks. making deposits, remotely opening deposit and loan accounts, performing online currency conversion operations, making payments from an international bank card account, and other remote banking services are widely used.